2021
DOI: 10.3389/fpubh.2021.778964
|View full text |Cite
|
Sign up to set email alerts
|

Development of Graves' Disease After SARS-CoV-2 mRNA Vaccination: A Case Report and Literature Review

Abstract: Background: Mounting evidence has revealed the interrelationship between thyroid and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to explain the thyroid dysfunction and autoimmune thyroid disorders observed after coronavirus disease 2019 (COVID-19). There are limited reports of thyroid dysfunction after SARS-CoV-2 vaccination.Methods: We report a case of a 40-year-old Chinese woman who developed Graves' disease after BNT162b2 mRNA vaccine. A search of PubMed and Embase databases from 1 Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 24 publications
(29 reference statements)
0
62
0
1
Order By: Relevance
“…The COVID-19 vaccine-associated GD cases published until the end of December 2021 and the current cases were summarized in Table 1 . It was identified that 13 GD cases associated with the COVID-19 vaccine have been reported [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. Eight (61.5%) of these cases were women, and the median age at diagnosis was 40 (range, 28–71) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 vaccine-associated GD cases published until the end of December 2021 and the current cases were summarized in Table 1 . It was identified that 13 GD cases associated with the COVID-19 vaccine have been reported [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. Eight (61.5%) of these cases were women, and the median age at diagnosis was 40 (range, 28–71) years.…”
Section: Resultsmentioning
confidence: 99%
“…From this point of view, the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection-associated autoimmune thyroid diseases (AITD) can be expected. Indeed, some cases of GD and other AITD have been reported following SARS-CoV-2 infection and its immunization [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. When considering the pre-COVID-19 period, in a case report published after the H1N1 pandemic, two newly-diagnosed autoimmune diseases (GD and narcolepsy type 1) had been detected following H1N1 vaccination in a 40-year-old female patient [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that portal infiltration with eosinophils correlates with drug-induced liver injury, including vaccines (i.e., Moderna mRNA-1273 and AstraZeneca ChAdOx1 nCoV-19 vaccines) [ 8 , 27 , 28 ]. This could partially explain the existence of hepatitis following vaccination without positivity for liver-associated autoantibodies ( Table 1 ) [ 8 , 10 , 12 , 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the exposure to vaccine adjuvants used as immunogenicity enhancing agents of the vaccine formulation [ 19 , 20 ] has been proposed to be capable of inducing diverse immune reactions [ 16 , 21 , 22 ]. This leads to the so-called Autoimmune/Autoinflammatory Syndrome Induced by Adjuvants (ASIA).…”
Section: Discussionmentioning
confidence: 99%
“…These two patients’ diagnoses were Graves’s disease. Literature review concerning cases reports in different countries regarding thyroid dysfunction after SARS-CoV-2 vaccination has shown a maximum time of onset after vaccination of 56 days [ 21 ]. In contrast and as it has recently been described [ 10 ], subacute thyroiditis triggered not by COVID-19 vaccination but by COVID-19 infection, seemed to take place 2–3 weeks after viral infection, and classic subacute thyroiditis (postviral) usually occurs within 2–8 weeks following viral infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%